U.S. R&D, 1975–1998 - Png, Ivan P. L. (Strategic Management Journal, 2019)
[Research Summary: Here, I document the governing copyright law and process of digitizing print records with specific application to the Jaques Cattell directories of U.S. R&D. This novel dataset covers 2,805 companies with 8,525 facilities, including location, reporting line within the organization, numbers of professional staff and technicians, and R&D fields over the years 1975–1998. The dataset includes a match to the Compustat identifier, gvkey. As an illustration, I use the new dataset to investigate the effect of organization structure on innovation. By contrast with previous research based on smaller samples, I find no significant relation between organization structure and innovation. Managerial Summary: Here, I document the governing copyright law and process of digitizing print records with specific application to the Jaques Cattell directories of U.S. R&D. This novel dataset covers 2,805 companies with 8,525 facilities, including location, reporting line within the organization, numbers of professional staff and technicians, and R&D fields over the years 1975–1998. The dataset is matched to Compustat. It can be used to study novel issues including (a) the effect of complementary manufacturing and marketing assets on how a company exploits its technological capabilities; (b) the relation between the centralization of the R&D organization and productivity of innovation; (c) how clusters influence the location of R&D facilities; and (iv) how state law affects the geography of R&D.]